BUILDING PURCHASE INTENTION BY MAXIMIZING SOCIAL MEDIA MARKETING AND CELEBRITY ENDORSEMENT FACTORS ON KANZLER PRODUCTS - Kennilyn, Thio; Saktiana, Galuh Mira (Graduate Program of Universitas Tarumanagara, 2025)
The consumption of processed meat products in Indonesia has increased and created increasingly fierce competition in the processed meat products industry. Kanzler, as one of the processed meat product brands, also feels tight competition. This study delves into the impact of social media marketing and celebrity endorsements on the purchase intention of Kanzler products with brand awareness acting as a mediating variable. The research employs the PLS-SEM analysis technique and quantitative descriptive design, which are both generated using the SmartPLS 4 software. This study involves non-probability sampling, specifically using purposive sampling techniques to collect data from 230 participants through an online survey conducted using Google Form. Based on the study results, purchase intention is boosted by social media marketing, celebrity endorsements, and brand awareness. Brand awareness is also boosted by social media marketing and celebrity endorsements. Social media marketing is connected to brand awareness and thus to purchase intention. In the meantime, the connection between purchase intention and celebrity endorsement stays unaffected by brand awareness. This research uncovers the factors that impact purchase intention and investigates inconsistencies through the Theory of Planned Behavior. This research can serve as a valuable resource for Kanzler and other marketers, assisting them in assessing and enhancing the effectiveness of their marketing strategies.